Self-Compassion Correlates of Anxiety and Depression Symptoms in Youth: A Comparison of Two Self-Compassion Measures - Peter Muris; Kris Bongers; Claudia Schenning; Cor Meesters; Henry Otgaar (MDPI AG, 2022)
Background and purpose: Self-compassion is considered as a protective psychological construct that would shield against the development of emotional problems. The aim of the present study was to compare the 'protective nature' of two measures of self-compassion: the Self-Compassion Scale for Youth (SCS-Y) and the Sussex-Oxford Compassion for the Self Scale (SOCS-S). Methods: Eighty-seven adolescents aged 12 to 18 years completed both self-compassion measures as well as scales of anxiety and depression symptoms. Results: SCS-Y and SOCS-S scores were positively correlated, and for both measures it was generally found that higher levels of self-compassion were associated with lower levels of emotional symptoms. However, the uncompassionate self-responding scales of the SCS-Y correlated positively with anxiety and depression symptoms and hence can better be seen as indices of vulnerability. Regression analyses suggested that a positive attitude toward oneself, as measured by the self-kindness scale of the SCS or its SOCS-S equivalent 'feeling for the person suffering' is particularly relevant as a buffer against emotional problems. Conclusion: The protective nature of self-compassion can be established by both measures. Caution is advised with the use of the uncompassionate self-responding scales included in the SCS-Y as they appear to measure vulnerability rather than protection.